Nanoscale insights into the damage tolerance of Cantor alloys at cryogenic temperatures. (15th July 2022) - Ji, Weiming; Wu, Mao S.
Highlights: Deformation mechanism maps are constructed to assess the plastic deformation. HCP to FCC phase transformation occurs due to the athermal dislocation cross-slip. Solid-state amorphization at grain boundaries leads to high damage tolerance. Design guidelines for Cantor alloys at cryogenic temperatures are proposed. Abstract: High-entropy alloys deform plastically and may also be at risk to fracture in extreme environments. In this paper, the damage tolerance of nanocrystalline Cantor alloys under mode I loading at cryogenic temperatures is investigated via molecular dynamics. We find that the damage tolerance is improved significantly with the decrease of temperature, in contrast to conventional metals. Deformation mechanism maps are constructed to assess the plasticity based on the grain size and temperature. Results show that the plastic deformation is governed by a synergy of face-centered-cubic to hexagonal closed-packed martensite transformation, twinning, stacking fault formation, grain boundary (GB) plasticity, and especially dynamic recovery. Specifically, a crossover from shear localization to solid-state amorphization is identified with the decrease of temperature and grain size. The amorphization at GBs dissipates larger strain energy, leading to precursor retardation and hence a high damage tolerance. A final deformation mechanism map is constructed to combine the deformation mechanisms and the crossover pathway from localization to amorphization. This map has great implications on improving the damage tolerance of Cantor alloy at cryogenic temperatures. Graphical Abstract: Graphical Abstract Image, graphical abstract .